A REVIEW ON ANTI-DIABETIC DIET IN AYURVEDA CLASSICS - Bhadran Sajitha; Eapen Jollykutty (International Journal of Ayurveda and Pharma Research, 2019)
Type 2 Diabetes Mellitus (Type2 DM) is affecting millions of people globally it is estimated that 425 million people (20–79 years of age) suffer from DM. Complications of DM can be simply prevented through lifestyle modifications and dietary interventions with good glycemic control. Aim and Objectives: This literal review is to compile whether standard Ayurveda Classics adequately mention the details of Anti Diabetic Diet (Padhyapadhyas in Pramehi). Life style modification and dietary interventions are remarkable in the management of Type 2 diabetes mellitus in Ayurvedic literature also. In this article review of Ayurvedic classical literatures is done to compile and analyze diabetic diet and its applications in detail. Materials and Methods: Standard textbooks of Ayurveda especially Bruhathrayis- Soothrasthanas and Chikitsasthanas of Ashtangahrudayam by Vagbhata, Charaka Samhitha by Punarvasu Athreya and Susrutha Samhitha by Lord Dhanwanthari, were analyzed to make conclusions on diabetic diet regimes to control Type II Diabetes Mellitus. Results:-Dietary advises given in Ayurveda classics are in a systematic way from cereals to different food items which can be utilized for diet plan in Type II Diabetes Mellitus with the help of current knowledge of glycemic index and glycemic load. Conclusion: This review article concentrates on the needy and uniform source of information regarding Anti-diabetic diet. On the base of this review conclusions were made on Ayurvedic dietary interventions in diabetes to get better results.